Enhancing HIV/AIDS Prevention in Adolescents: An Information- Motivation-Behavioral Skills Approach - Muthar, Muhtar; Julhana, Julhana; Sri Djuwitaningsih; Komang Ayu Henny Achjar; Fadlurrahmi Fadlurrahmi (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine how adolescents’ knowledge and attitudes regarding HIV/AIDS prevention were affected by health education using a motivational information approach. METHODOLOGY: This study employed a quasi-experimental design conducted in Bima, NTB, Indonesia, from July 2024 to January 2025. A cluster sampling technique was used, yielding a total of 374 students divided into two groups. The control group received HIV/AIDS educational materials in the form of textbooks without support from cadres. In contrast, the intervention group was given a booklet about HIV/AIDS and received guidance from a cadre. The intervention was carried out four times a week for six months. Data analysis was performed using a paired t-test. RESULTS: The intervention significantly improved knowledge and attitudes towards HIV/AIDS prevention in adolescents, regardless of the control or intervention group. The intervention group showed a significant increase in knowledge scores about HIV/AIDS, with an average score of 13.74, compared to the control group’s 8.04. The intervention group also showed a significant increase in attitude scores, with an average of 47.12, compared to the control group’s average of 35.04. Both knowledge and attitude in the intervention group had p-values of <0.000. CONCLUSION: The intervention proved to be more effective in improving knowledge and attitudes towards HIV/AIDS.